PSXIII-18 Conceptus stimuli in peripheral blood mono and polymorphonuclear cells at the beginning of pregnancy. (5th December 2019) - Melo, Gabriela Dalmaso de; Motta, Igor Garcia; Rocha, Cecilia Constantino; Diaza, Angela Maria Gonella; Silveira, Juliano Coelho da; Binelli, Mario; Pohler, Ky; Pugliesi, Guilherme
Abstract: The objective of this experiment was to compare the expression of Interferon-tau Stimulated Genes (ISGs) in peripheral blood mono and polymorphonuclear cells (PBMCs and PMNs) in heifers following insemination. Twenty-nine Nelore heifers had estrous cycle synchronized, and FTAI occurred on D0. Pregnancy diagnosis was performed by ultrasonography on D28 post FTAI. On D0, 10, 14, 16, 18 and 20, blood (25mL) from the jugular vein was collected in heparinized tubes for isolation of PMNs and PBMCs. The isolation was performed using Ficoll®Paque Plus (GE Healthcare). PMNs and PBMCs samples from 8 pregnant and 9 non-pregnant heifers were subjected to RNA extraction using the DirectZol-RNA kit (Zymo-Research) and Trizol (Invitrogen), respectively. The expression of the target genes (ISG15, OAS-1, MX1 and MX2) was normalized in relation to the two reference genes (GAPDH/ACTB for PMNs and GAPDH/PPIA for PBMCs). The abundance of transcripts was evaluated by analysis of variance considering fixed effects of group, day and group by day interaction using the PROC MIXED procedure in SAS. PMNs and PBMCs had a similar expression profile of ISG15 and OAS-1, showing a relative increase (P < 0.05) from D18, and a significant increase in (P < 0.05) expression in pregnant compared to non-pregnant females on D18 and D20. These results were also observed for MX1 in PBMCs. In PMNs, no significant effects for MX1 were found. For MX2, in both cells types, only a group effect (P < 0.05) was observed, indicating a higher expression in pregnant heifers (0.57±0.11 vs. 0.21±0.03) on the days evaluated. When comparing the relative expression of the target genes to D0, no significant (P > 0.1) differences were found between PMNs and PBMCs. In summary, ISG expression is similar in PMNs and PBMCs, specifically for ISG15 and OAS-1, which both seem to be suitable biomarkers for potential early pregnancy determination in heifers.